Polishing a Crystal: Understanding Plato’s Allegory of the Cave - Purdy, Nick (The Oracle, 2021)
Behold! He was born into chains and constrained to a chair. His head was held still, looking forwards. The world flickered as shadows on the wall in front of him. These shadows were life as he understood it; but he is being released. He is now being dragged out of this shadowy reality and into the light of actual objects. His eyes must adapt to the painful sunlight. And, once they have and he can see clearly the world as it is around him, he must return to the world of shadows. This is the philosopher. Plato’s allegory of the cave, summarized above, expresses Socrates’ understanding of the philosopher, his role in society, and the experience one needs to become a philosopher. Here, we will offer an interpretation of this famous allegory from Plato’s Republic to uncover the nature of the philosopher according to Socrates. To do so, we will examine the life experiences of the philosopher; his guiding principles and how he must come to arrive at them; and the practical use of philosophy within the polis. Moreover, we will examine these points with careful reference to the allegory of the cave and thereby reveal the allegory’s powerful ability to express Socrates’ notion of the philosopher.